Taxonomic notes on the genus Pseudodynerus (Hymenoptera, Vespidae, Eumeninae) - Hermes,Marcel G. (2005)
The differences between Pseudodynerus auratoides (Bertoni, 1918) and Pseudodynerus serratus (Fox, 1902) are established. Lectotypes of Stenodynerus mondaiensis Bertoni, 1918 and Stenodynerus auratoides Bertoni, 1918 are designated. Pseudodynerus penicillatus (Zavattari, 1912) is redescribed and newly raised from synonymy under P. serratus (Fox, 1902).